Improved genome assembly provides new insights into genome evolution in a desert poplar (Populus euphratica). (4th March 2020) - Zhang, Zhiyang; Chen, Yang; Zhang, Junlin; Ma, Xinzhi; Li, Yiling; Li, Mengmeng; Wang, Deyan; Kang, Minghui; Wu, Haolin; Yang, Yongzhi; Olson, Matthew S.; DiFazio, Stephen P.; et al.
Abstract: Populus euphratica is well adapted to extreme desert environments and is an important model species for elucidating the mechanisms of abiotic stress resistance in trees. The current assembly of P. euphratica genome is highly fragmented with many gaps and errors, thereby impeding downstream applications. Here, we report an improved chromosome‐level reference genome of P. euphratica (v2.0) using single‐molecule sequencing and chromosome conformation capture (Hi‐C) technologies. Relative to the previous reference genome, our assembly represents a nearly 60‐fold improvement in contiguity, with a scaffold N50 size of 28.59 Mb. Using this genome, we have found that extensive expansion of Gypsy elements in P. euphratica led to its rapid increase in genome size compared to any other Salicaceae species studied to date, and potentially contributed to adaptive divergence driven by insertions near genes involved in stress tolerance. We also detected a wide range of unique structural rearrangements in P. euphratica, including 2, 549 translocations, 454 inversions, 121 tandem and 14 segmental duplications. Several key genes likely to be involved in tolerance to abiotic stress were identified within these regions. This high‐quality genome represents a valuable resource for poplar breeding and genetic improvement in the future, as well as comparative genomic analysis with other Salicaceae species.